2022
DOI: 10.1177/01626434221085554
|View full text |Cite
|
Sign up to set email alerts
|

Increasing On-Task Behavior Using Technology-Based Self-Monitoring: A Meta-Analysis of I-Connect

Abstract: Self-monitoring is a promising evidence-based intervention for students who benefit from supplemental supports to stay on-task during academic periods. I-Connect, a technology-based self-monitoring intervention with a substantial body of research, allows students to discretely recognize and record their behavior on a mobile or desktop app at scheduled intervals, to improve positive behavior and increase inclusion opportunities. This meta-analytic review examined the effect of I-Connect on the on-task behavior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 34 publications
2
21
0
Order By: Relevance
“…Self-monitoring is based on the theory of reactivity (Nelson & Hayes, 1981), which states that the act of monitoring makes a person more aware of their behavior, and this awareness consequently changes the behavior being monitored. Although initially used in therapeutic settings, researchers have demonstrated that self-monitoring can also be applied in educational settings where students can monitor their attention to or performance on a task (Cook et al, 2017; Scheibel et al, 2023).…”
Section: Self-monitoringmentioning
confidence: 99%
“…Self-monitoring is based on the theory of reactivity (Nelson & Hayes, 1981), which states that the act of monitoring makes a person more aware of their behavior, and this awareness consequently changes the behavior being monitored. Although initially used in therapeutic settings, researchers have demonstrated that self-monitoring can also be applied in educational settings where students can monitor their attention to or performance on a task (Cook et al, 2017; Scheibel et al, 2023).…”
Section: Self-monitoringmentioning
confidence: 99%
“…In [ 28 ], a meta-analysis was conducted on studies using the I-Connect mobile app to increase on-task behavior. The I-Connect app was designed to allow an individual to perform self-monitoring towards the goal of improving positive behaviors.…”
Section: Rq2: What Are the Primary Purposes Of The Mobile Apps?mentioning
confidence: 99%
“…On-task behavior was the most common outcome measured using I-Connect across the evidence base. Meta-analysis of these studies found an average effect of I-Connect for on-task behavior is LRRi = 0.86 (95% confidence interval [CI] = [0.68, 1.04]), and an unweighted average percentage change across conditions was found to be 198% (range = 19%-834%) across intervention packages (Scheibel et al, 2023). Variations were noted across intervention packages, including (a) student training session durations and methods, (b) monitoring intervals, and (c) session lengths.…”
Section: I-connect Evidence Basementioning
confidence: 99%